2005
DOI: 10.1088/0954-3899/31/8/014
|View full text |Cite
|
Sign up to set email alerts
|

Density functional theory: methods and problems

Abstract: Abstract. The application of density functional theory to nuclear structure is discussed, highlighting the current status of the effective action approach using effective field theory, and outlining future challenges.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
211
1
1

Year Published

2005
2005
2011
2011

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(219 citation statements)
references
References 12 publications
6
211
1
1
Order By: Relevance
“…The obtained neutron-skin thicknesses are smaller than the calculations by the relativistic mean field (RMF) [17]. (It was pointed out that RMF calculations overestimate neutron-skin thicknesses [33]. )…”
Section: Calculationsmentioning
confidence: 68%
“…The obtained neutron-skin thicknesses are smaller than the calculations by the relativistic mean field (RMF) [17]. (It was pointed out that RMF calculations overestimate neutron-skin thicknesses [33]. )…”
Section: Calculationsmentioning
confidence: 68%
“…The reason for this is related to the difference in the nuclear symmetry energy and, consequently, to the different neutron equation of state (EOS) which has been extensively studied in recent years [51][52][53][54]. It was shown that there exists a linear correlation between the derivative of the neutron EOS (or the pressure of neutron matter) and the neutron skin thickness in heavy nuclei (defined as r np = r n − r p ) in both Skyrme HF [55,56] and RMF [56,57] models. We note that also a relation between r np and both volume and surface symmetry energy parameters was established recently by Danielewicz [58] and Steiner et al [59] which provides a consistent description of nuclei with neutron excess.…”
Section: Fig 4 Difference Between Neutronmentioning
confidence: 99%
“…It has been shown that the neutron skin thickness in heavy nuclei, like 208 Pb, calculated in mean-field models with either nonrelativistic or relativistic effective nuclear interactions, displays a linear correlation with the slope of the neutron equation of state (EOS) obtained with the same interactions at a neutron density ρ ≈ 0.10 fm −3 [37][38][39]. A similar correlation exists between R np and the density derivative of the bulk symmetry energy [13][14][15][16]33,40,41], as the latter is a measure of the pressure difference between neutrons and protons. These correlations have been exploited in recent years to gain a deeper understanding of the isospin properties of the effective nuclear interaction and to relate them with nuclear and astrophysical observations.…”
Section: Introductionmentioning
confidence: 96%